Padiksan Ceremony Management in Bali, Understanding the Synergy of Padiksan Ceremonies, Case Study of Balinese Culture - Wijaya, I Wayan Kandi; Yadnyana, Ketut; Amrita , Nyoman Dwika Ayu; Sumada, I Made (International Journal of Psychosocial Rehabilitation, 2020)
Bali has a distinctive culture, famous for their customs as a frame of Hindu religion, adopted by the community, which is full of variety ceremonies. In the execution ceremony of Panca Yadnya, it needs priests or Sulinggih called as Master of Ceremonies. Despite the existence of hundreds of Sulinggih, the amount is still felt limited compared to the ceremony held in Bali. Very few people want to be Sulinggih, due to various reasons. For people who want to be Sulinggih, it can be done through the process of implementation of diksa Ceremony with Padiksan. The success of Padiksan is determined by some factors like 1), Nabe, 2). Learning systems (aguron- guron, 3). The ceremony, 4). Management, 5). Supporting tools of social and economic. Management plays an important role in managing the various activities of the Padiksan ceremony, and in order to reach Padiksan’s goal that is to make a new Sulinggih be born to serve the people. The purpose of this research is to give better understanding about Management Padiksan Ceremony. Methodology used to collect the data was Homogeneus sampling, (determination of the specific sample homogeneus and researching in depth), and systematic purpose sampling in which respondents were uncertain. Processing and analysis data used NVIVO software application. the success of Padiksan ceremony was determined by management, where traditional management synergize with management conventional. Value, improving the quantity and quality of Sulinggih in Bali.